Der Untergang - Klausmann, Rainer 1949-; Eichinger, Bernd 1949-2011; Eichinger, Bernd 1949-2011; Ganz, Bruno 1941-2019; Lara, Alexandra Maria 1978-; Harfouch, Corinna 1954-; Köhler, Juliane 1965-; Noethen, Ulrich 1959-; Kretschmann, Thomas 1962-; Ferch, Heino 1963- (Constantin Film, 2005)
Film dramatizing the last days of Hitler and his associates.
Extras: Blick hinter die Kulissen (circa 10 Minuten) ; Interviews (circa 5 Minuten)
Original: Deutschland, 2004
Sprache: Deutsch ; Untertitel: Deutsch für Hörgeschädigte
Keywords: Hitler, Adolf <1889-1945> -- Death and burial -- Drama; Berlin, Battle of, Berlin, Germany, 1945 -- Drama; Feature films; Films for the hearing impaired; Film; DVD-Video